St. Athanasius' Orations against the Arians in the 1st Bulgarian Kingdom (Forum Theologicum Sardicense, 2025)
The present paper gives an overview of the Medieval Bulgarian translationsof St. Athanasius' Against the Arians. It analyses the historical andpastoral reasons of the Ecumenical Patriarchate to promote this text in theBulgarian milieu of the 10th century.
Keywords: Athanasius of Alexandria; Ecumenical Patriarchate; Medieval Bulgarian Literature; Translations; 1st Bulgarian Kingdom; Patristics